TRACK VIDEO ANALYSIS AS PHYSICS MEDIA RESEARCH DURING 2016 TO 2020 A BIBLIOMETRIC ANALYSIS (IPF: Inovasi Pendidikan Fisika, 2022)
The purpose of this research is (1) To identify the distribution of articles related to the use of TVA as a medium in publications over the past 5 years; (2) To identify the distribution of languages used in the writing of TVA publications; (3) To identify the number of TVA scientific publications as Physics media research; (4) To identify the correlation between subjects used in TVA. The method used in this research is bibliometric analysis that can help researchers in researching the contents of bibliographies, analyzing the correlation of objects from Scopus metadata in the last 5 years, namely 2016 - 2020. From the search results on Scopus with the keyword TVA obtained as many as 24,495 documents. There are three dominant groups, namely Study, State, and Object. TVA deals with studies, research models and learning, related to tracking an object or benchmark, related to community activities or activities in a country.